A randomized trial of on-pump beating heart and conventional cardioplegic arrest in coronary artery bypass surgery patients with impaired left ventricular function using cardiac magnetic resonance imaging and biochemical markers. - Pegg, T; Selvanayagam, J; Francis, J; Karamitsos, T; Maunsell, Z; Yu, L; Neubauer, S; Taggart, D (2008)
BACKGROUND: Beating heart coronary artery bypass grafting (CABG) improves early postoperative cardiac function in patients with normal ventricular function, but its effect in patients with impaired function is uncertain. We compared a novel hybrid technique of on-pump beating heart CABG (ONBEAT) with conventional on-pump CABG (ONSTOP) in patients with impaired ventricular function. METHODS AND RESULTS: In a single-center randomized trial, 50 patients with impaired ventricular function were randomly assigned to ONBEAT or ONSTOP. Patients underwent cardiac magnetic resonance imaging for function and delayed hyperenhancement early and later after surgery. Serial assessment of biochemical markers was also undertaken. Preoperative characteristics were well matched; cardiac index was 2.85+/-0.53 (ONBEAT) and 2.62+/-0.59 L x min(-1) x m(-2) (ONSTOP). Early after surgery, there was a trend toward a greater reduction in end-systolic volume index in ONSTOP patients versus ONBEAT (-9+/-8 versus -4+/-11 mL x m(-2); P=0.06). The changes were sustained and significant at 6 months (-14+/-18 versus -2+/-19 mL x m(-2); P=0.04). Furthermore, the incidence of new hyperenhancement at 6 days was higher in ONBEAT patients (P=0.05), with 6 of 17 (35%) sustaining 8.2+/-5.2 g of new hyperenhancement each versus 2 of 23 (9%) in the ONSTOP group, each with 9.8+/-9.0 g (P=0.86). Finally, median area under the curve for troponin was higher in ONBEAT at 461 (interquartile range, 226 to 1141) microg/L versus 160 (interquartile range, 98 to 357) microg/L for ONSTOP (P=0.002). CONCLUSIONS: The incidence of new irreversible myocardial injury was significantly higher in ONBEAT than in ONSTOP patients. Furthermore, at 6 months, only ONSTOP patients demonstrated an improvement in ventricular geometry. The most likely mechanism is inadequate coronary perfusion to distal myocardial territories in patients with severe proximal coronary disease.